2008
DOI: 10.5713/ajas.2008.70408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Galacto-mannan-oligosaccharides or Chitosan Supplementation on Cytoimmunity and Humoral Immunity in Early-weaned Piglets

Abstract: Immunomodulatory feed additives might offer alternatives to antimicrobial growth promoters in pig production. This experiment was designed to determine the effects of dietary galacto-mannan-oligosaccharide (GMOS) and chitosan oligosaccharide (COS) supplementation on the immune response in early-weaned piglets. Forty 15-day-old piglets (Duroc×Landrace×Yorkshire) with an average live body weight of 5.6±0.51 kg were weaned and randomly assigned to 4 treatment groups that were fed maize-soybean meal diets containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
58
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 35 publications
6
58
1
1
Order By: Relevance
“…IL-1) microenvironment (Schley and Field 2002). The study showed that CHI enhanced the serum level of IL-1 and its gene expression in lymph nodes and jejunal mucosa compared to supplementation with lincomycin in early-weaned piglets (Yin et al 2008). The sCD4 and sCD8 in peripheral blood represented the soluble form of CD4 + and CD8 + , which could reflect the activation of T cells (Uehara et al 2003).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…IL-1) microenvironment (Schley and Field 2002). The study showed that CHI enhanced the serum level of IL-1 and its gene expression in lymph nodes and jejunal mucosa compared to supplementation with lincomycin in early-weaned piglets (Yin et al 2008). The sCD4 and sCD8 in peripheral blood represented the soluble form of CD4 + and CD8 + , which could reflect the activation of T cells (Uehara et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Lim et al (1997) showed that concentrations of IgG, IgA, and IgM in mesenteric lymph node (MLN) lymphocytes were generally higher in rats fed CHI than in those fed cellulose. Furthermore, dietary supplementation of CHI in piglets increased serum immunoglobulins and recouped a loss which was caused by early weaning (Yin et al 2008;Li et al 2013). Xiao et al (2013) added 50 mg/kg chlortetracycline or 300 mg/kg CHI in the diet of weaned piglets and showed that the expression of jejunal mucosal secretory IgA (sIgA) protein was higher in the CHI group than in both control and chlortetracycline groups, which indicated CHI could improve the intestinal mucosal immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan is a natural alkaline polysaccharide with positive charges, and also one of the most abundant natural polymers [5]- [7]. As a nontoxic, biodegradable carbohydrate polymer [8] it contains amino and hydroxyl groups per residue [9] which gives chitosan many biological activities, such as haemostatic [10], anti-inflammatory [11], antitumor activity [12] [13], antimicrobial activity [15], hypoglycemic and hypo cholesterolemic activity [16] [17] and an immune-stimulatory effect [18] [19].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan has been shown to be an ideal additive to promote systemic and mucosal immune functions of animals. Yin et al (2008) indicated that chitosan might enhance the doi: 10.17221/8405-CJAS cell-mediated immune response in early-weaned piglets by modulating the production of cytokines and antibodies. Porporatto et al (2005) found that the uptake of chitosan involved the antigenpresenting cells in the intestinal of rats after oral administration, and this mucoadhesive polysaccharide profoundly affected intestinal immunity by enhancing the T helper cell type 2 (Th2)/Th3 microenvironment in the mucosa.…”
Section: Introductionmentioning
confidence: 99%